Transcriptome analysis of the hepatopancreas from the Litopenaeus vannamei infected with different flagellum types of Vibrio alginolyticus strains - Zhang, Jingwen; Liu, Kaifang; Gong, Xiaoxiao; Zhang, Na; Zeng, Yanhua; Ren, Wei; Huang, Aiyou; Long, Hao; Xie, Zhenyu (Frontiers in Cellular and Infection Microbiology, 2023)
Vibrio alginolyticus, one of the prevalently harmful Vibrio species found in the ocean, causes significant economic damage in the shrimp farming industry. Its flagellum serves as a crucial virulence factor in the invasion of host organisms. However, the processes of bacteria flagella recognition and activation of the downstream immune system in shrimp remain unclear. To enhance comprehension of this, we conducted a study involving a V. alginolyticus mutant strain with different flagellum types and investigated the gene expressions in shrimp hepatopancreas infected with these strains. Specifically, we created a △flhG strain by in-frame deletion of the flhG gene in V. alginolyticus strain HN08155. The △flhG strain, unlike the wild type, lost its ability to regulate flagella numbers negatively and displayed multiple flagella. To examine the immune responses in Litopenaeus vannamei hepatopancreas after being infected with different strains, we utilized the transcriptome analysis. The results revealed upregulation of several immune-related genes in the shrimp hepatopancreas when infected with the hyper flagella type strain. Notably, two C-type lectins (CTLs), namely galactose-specific lectin nattectin and macrophage mannose receptor 1, were found to be potentially involved in flagella recognition. Furthermore, the TNF receptorassociated factor (TRAF) 6 gene was upregulated in the hepatopancreas, suggesting activation of the immune system through the TRAF6 pathway upon flagella detection by CTLs. These findings offer new insights into the recognition and response of shrimp to bacteria flagella.